Comparison of various treatments for irritable bowel syndrome. - Ritchie, J A (1980)
A previous therapeutic trial of factorial design showed that a combination of a psychotropic drug, a smooth-muscle relaxant, and a bulk former (lorazepam, hyoscine hydrobromide, and ispaghula husk) relieved symptoms of the irritable bowel syndrome more effectively than the same agents given singly. Another trial of similar design was undertaken to compare each of these three agents with another having the equivalent clinical actions--namely, Motival (fluphenazine/nortriptylene mixture), mebeverine, and bran. Ninety-six patients took part; all received three agents, one from each of the three pairs being compared, and no placebos were used. Fifty-six patients reported a sustained symptomatic improvement, which was a significantly higher incidence than in the previous trial, when placebos were used. Ispaghula was significantly more effective than bran. The combination of ispaghula, Motival, and mebeverine improved 11 out of 12 patients--significantly more than bran, Motival, and hyoscine (five improved), or bran, lorazepam, and mebeverine (four improved). Mebeverine was significantly more effective when combined with Motival (18 out of 24 improved) than with lorazepam (10 improved). These results confirm the value of a combined therapeutic approach to the relief of the irritable bowel syndrome and suggest the possibility of synergism between agents.